Technical Possibilities of Reducing the Sound Pressure Level Emitted into the Environment by a Power Transformer - BORUCKI, Sebastian; BOCZAR, Tomasz; CICHON, Andrzej (Archives of Acoustics, 2011)
The subject presented in this paper refers to measurements and assessment ofthe corrected sound pressure level values (noise) occurring around a medium-powertransformer. The paper presents the values of noise accompanying the operation ofthe power object before and after its modernization, which consisted in repeatedcore pressing and replacement of the cooling system. The main aim of the researchwork was the assessment of the influence of the repair work on the noise level emittedinto the environment.